If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=12-x/3
We move all terms to the left:
x-(12-x/3)=0
We add all the numbers together, and all the variables
x-(-x/3+12)=0
We get rid of parentheses
x+x/3-12=0
We multiply all the terms by the denominator
x*3+x-12*3=0
We add all the numbers together, and all the variables
x+x*3-36=0
Wy multiply elements
x+3x-36=0
We add all the numbers together, and all the variables
4x-36=0
We move all terms containing x to the left, all other terms to the right
4x=36
x=36/4
x=9
| 90=(5x+5)+(3x+5) | | 2x+4=6x+4 | | X+3x-12=0 | | -9-+6=-x+4 | | 6x+8=5+10 | | 6x+8x=5+10 | | x*3=0.125 | | 8x-10=90-12x | | 8(x−4)=−96 | | 8(x−4)=−96* | | 5x(x-3)=2x+6 | | 0x=-31 | | 7(2x-5)-3(x-5)=3+(5x-5) | | 5a-6=10-(-a) | | 7-(3m+3)/6=0 | | 45-(5s+12)=-4s,s= | | -4x^2-5x+12=0 | | k=-2(k-9) | | -0.5p+1.8=0.4p | | −4x−24=8x+72. | | -2+a=7a/9 | | 2m-1=-6+3m | | A=x²-16 | | 1/x+1/3x=1/60 | | (10x-1)(3+4x)=0 | | 23+2x-1/3=34+6x-1/12 | | -7t-3=60 | | 4x-70=9x-5 | | 3x2-2x+2=0 | | 3x2+11x+2=0 | | 8x-11=10x+6 | | -k^2+2k-5=-3 |